Achievement of Therapeutic Vancomycin Trough Serum Concentrations with Empiric Dosing in Neonatal Intensive Care Unit Patients. Issue 7 (July 2015) - Ringenberg, Theresa; Robinson, Christine; Meyers, Rachel; Degnan, Lisa; Shah, Pooja; Siu, Anita; Sturgill, Marc
Abstract : Background: The recommended goal serum trough concentration for vancomycin has increased to 10 to 20 mcg/mL, with a higher range of 15 to 20 mcg/mL for serious infections due to methicillin-resistant Staphylococcus aureus in children and adults. Although neonatal references have also recommended these higher target concentrations, dosing recommendations remained unchanged. The objective of this study was to assess the percentage of neonates and young infants achieving a serum trough concentration between 10 and 20 mcg/mL with empiric vancomycin dosing based on Neofax ® in a neonatal intensive care unit (NICU) population. Methods: A multi-institutional retrospective chart review was conducted to identify NICU patients who received a minimum of three doses of intravenous vancomycin and had at least one appropriately drawn trough. Additional outcomes included the duration of vancomycin therapy, number of dose adjustments required to attain goal trough concentrations, time to goal trough, and incidence of nephrotoxicity and ototoxicity. Results: Of the 171 vancomycin serum trough concentrations included in the primary outcome, only 25.1% achieved a goal trough of 10 to 20 mcg/mL with empiric dosing. Only 44.6% of patients achieved the goal trough of 10 to 20 mcg/mL at any time during their vancomycin therapy. The average gestational age was 28.2 ± 4.1 weeks, average postnatal age at start of vancomycin was 34.1 ± 34.6 days, and average weight of the patients at start of vancomycin was 1602 ± 1014.5 g. The average and median total daily dose in those patients who achieved an initial vancomycin trough of 10–20 mcg/mL were 32.4 mg/kg/day and 30 mg/kg/day, respectively. Conclusion: Dosing of vancomycin based on Neofax ® in NICU patients is insufficient in yielding serum trough concentrations of 10 to 20 mcg/mL. Further studies are needed to evaluate the optimal dosing regimen to achieve higher trough concentrations in this patient population.